A Ministudy of Employee Turnover in US Hospitals. Issue 1 (January 2015) - Collins, Sandra K.; McKinnies, Richard C.; Matthews, Eric P.; Collins, Kevin S.
<x xml:space="preserve">Abstract</x> A ministudy was conducted to collect self-reported employee turnover rates in US hospitals. The results indicate many hospitals are struggling with high employee turnover rates. Widespread variances in ratings were observed across hospitals, which may be due to lack of consistency in how they each calculate their employee turnover. This makes benchmarking for the purposes of performance improvement challenging.